Tinjauan Yuridis Penyelesaian Wanprestasi Dalam PerjanjianKredit Dengan Jaminan Hak Tanggungan(Studi Kasus Kantor Pelayanan Kekayaan Negara Dan Lelang Kota Surakarta) - Pramudya, Rheza Gellary, Septarina Budiwati, S.H., M.H, Darsono, S.H., M.H (2016)
This study aims to determine the process of settlement of default in the credit agreement with the guarantee of the right of dependents and any obstacles that arise in the process of settlement of defaulting on bail encumbrance through the auction at the State Property Office and Auction (KPKNL) of Surakarta. This research method through normative juridical approach with primary data in the form of interviews and secondary data derived from the materials library. Data were collected by literature study and interviews and then analyzed by qualitative analysis. The results showed that the completion of the defaults in the credit agreement with the guarantee of the right of dependents are in accordance with Act No. 4 of 1996 on Mortgage in Article 6, that if the debtor in default, the creditor or the first holder can sell the security rights object collateral through public auction and take repayment of the sale of collateral object. Obstacles in the completion of default by the guarantee of the right of dependents through the auction, which is the owner of the object guarantees long hindered the winning bidder for control objects warranties, so the winner of the auction incorporate these issues to the authorities (police) and even up to the court to assist the emptying of the object guarantees.